Reuse of Pan-milled P-XLPE cable powder as additive for asphalt to improve thermal stability and decrease processing viscosity. (26th April 2021) - Sun, Fasen; Yang, Shuangqiao; Bai, Shibing; Wang, Qi
Highlights: There was stronger intermolecular interaction between the P-XLPE cable powder and asphalt matrix. Presence of P-XLPE cable powder could effectively improve the compatibility between the rubber powder and asphalt matrix. Stable lamellar continuous phase was an ideal microstructure for polymer-modified asphalt mixtures. Abstract: The recycling of cross-linked polymer waste is a great challenge for the polymer recycling industry. In this research, the main objective was to investigate the feasibility of using waste peroxide cross-linked polyethylene (P-XLPE) cable powder on modified asphalt products by solid-state shear milling technology. Microscopic observation, FTIR analysis, DSC and TG experiments were carried out to study the properties and mechanism of asphalt modification with P-XLPE cable powder. The experimental results indicated, that the mechanism for traditional rubber powder modified asphalt involved physical swelling, resulting in poor performance. For P-XLPE modified asphalt, the P-XLPE powder and asphalt matrix were melted together and formed a unique twisted continuous phase during the modification process. The modification principle and special molecular structures of the polymer could further improve the compatibility and intermolecular interaction between the asphalt and P-XLPE materials, which resulted in an increase in the soluble content and a decrease in the processing viscosity. The high temperature (150 °C) viscosity of asphalt modified mixtures by P-XLPE cable powder decreased from 6.83 Pas of rubber powder modified asphalt to 3.68 Pas. The storage stability test further confirmed that P-XLPE modified asphalt had better high-temperature stability due to the stronger intermolecular interaction of the two polymer domains.